Time Complexity of Distributed Topological Self-stabilization: The Case of Graph Linearization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (LATIN 2010: Theoretical Informatics, 9th Latin American Symposium, Oaxaca, Mexico, April 19-23, 2010. Proceedings)

Brief announcement: towards robust medium access in multi-hop networks - Richa, Andrea W.; Zhang, Jin; Scheideler, Christian; Schmid, Stefan (Proceedings of the 29th Annual ACM Symposium on Principles of Distributed Computing, PODC 2010, Zurich, Switzerland, July 25-28, 2010)

A Jamming-Resistant MAC Protocol for Multi-Hop Wireless Networks - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Brief Announcement: Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Algorithms for Sensor Systems - 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers

Selected properties of a joint congestion controller for TCP connections - Savorić, Michael; Karl, Holger; Wolisz, Adam (Providing Quality of Service in Heterogeneous Environments, Proceedings of the 18th International Teletraffic Congress - ITC-18)

ANALYSING CAPACITY IMPROVEMENTS IN WIRELESS NETWORKS BY RELAYING - Karl, Holger; MENGESHA, S. (Wireless LANs and Home Networks)

ANY l-STATE ANALYTICAL SOLUTIONS OF THE KLEIN–GORDON EQUATION FOR THE WOODS–SAXON POTENTIAL - BADALOV, V. H.; AHMADOV, H. I.; BADALOV, S. V. (International Journal of Modern Physics E)
The radial part of the Klein–Gordon equation for the Woods–Saxon potential is solved. In our calculations, we have applied the Nikiforov–Uvarov method by using the Pekeris approximation to the centrifugal potential for any l-states. The exact bound state energy eigenvalues and the corresponding eigenfunctions are obtained on the various values of the quantum numbers n and l. The nonrelativistic limit of the bound state energy spectrum was also found.

Ausschau halten nach den Toten. Marcel Beyers Spurensuche im Feld der Familie - Eke, Norbert Otto (Deutsche Familienromane. Literarische Genealogien und internationaler Kontext)

„Jetzt aber Schluß!“ – Verwerfungen im Erinnerungsraum des frühen Nachkriegstheaters - Eke, Norbert Otto („Wacht auf, denn eure Träume sind schlecht!“ Literatur in den Anfangsjahren der Bundesrepublik Deutschland)

„Es ist alles wahr, was man hört.“ Die Shoah im Spiegelraum des westdeutschen Nachkriegstheaters - Eke, Norbert Otto (Die ersten Stimmen. Deutschsprachige Texte zur Shoah 1945-1963 / Les premières voix. Écrits sur la Shoah en langue allemande 1945-1963)

Der törichte Freiherr und die vernünftige Negerin. Ethnische Codierungen in Lafontaines Leben und Thaten des Freiherrn Quinctius Heymeran von Flaming - Eke, Norbert Otto (August Lafontaine (1758-1831). Ein Bestsellerautor zwischen Spätaufklärung und Romantik)

KeimZellen: Familie – Staat – Terrorismus - Eke, Norbert Otto (Familien Erzählen. Das literarische Werk John von Düffels)

„Heilig bleibt das Vaterland“. Konfigurationen des Nationalen im Historischen Drama der Restaurationszeit - Eke, Norbert Otto (Von der Spätaufklärung zur Badischen Revolution. Literarisches Leben in Baden zwischen 1800 und 1850)

Dorothee Hemme, Markus Tauschek (Hg.), Leben im Weltkulturerbe. Ethnologische Skizzen zum alltagskulturellen Umgang mit dem Prädikat UNESCO-Welterbe“, Göttingen 2008 - Seng, Eva- Maria (Bayerisches Jahrbuch für Volkskunde)

Simulating Tightly Intermeshing, Co-Rotating Twin Screw Extruders with SIGMA - Kretzschmar, Nils; Schöppner, Volker (Proceedings of the 2010 Summer Computer Simulation Conference)
A large proportion of plastics today is compounded, which means the process from refining a raw material to the processable material. For this process compounding extruders are used which mostly involve tightly intermeshing, co-rotating twin screw extruders. These extruders consist of two closely spaced screws which rotate in the same direction and convey the raw material to the screw tip. These screws are surrounded by several barrel modules which heat or cool the material. As the whole design of the machine is modularly arranged the process behavior of a twin screw extruder depends for the main part on the arrangement of the screw and the barrel elements. Until today this arrangement and process optimization is conducted by experienced engineers and with the help of trial-and-error methods. Furthermore, theoretical models are used with which the behavior of the extruder is estimated. As these models are mostly very complex they are only made available with the realization in different software projects. One of the tools is called SIGMA. Within this paper SIGMA is introduced as a software to optimize a twin screw extruder. SIGMA supports the engineer already in the early stages of the extruder arrangement.
Keywords: process optimization; polymer engineering; compounding; twin screw extruder; simulation

Brain activity in goal-directed movements in a real compared to a virtual environment using the Nintendo Wii. - Baumeister, Jochen; Reinecke, K; Cordes, M; Lerch, C; Weiss, M (Neurosci Lett)

Motor control and brain activity after prolonged exhaustive exercise: neurophysiological insights into fatigue - Baumeister, Jochen; Reinecke, K; Schubert, M; Weiss, M

Exhaustive exercise leads to changes in cortical activity and cognitive funktion - Baumeister, Jochen; Reinecke, K; Schubert, M; Weiss, M (Abstract Book - 15th Annual Congress of the European College of Sports Science)

Requirements and profile of German professional basketball - Schnittker, R; Baumeister, Jochen; Paier, D; Wilhelm, P; Weiss, M

The required number of epochs for representing brain states from spontaneous EEG - Schubert, M; Reinecke, K; Schade, J; Weiss, M; Baumeister, Jochen (ISEK 2010 - Scientific Program)

Altered brain activity after an exhaustive strength training - Reinecke, K; Schubert, M; Weiss, M; Baumeister, Jochen (Abstract Book - 15th Annual Congress of the European College of Sports Science)

The effect of visual perturbation during drop landings - Koplin, S; Kirchner, C; Koschate, J; Weiß, M; Baumeister, Jochen (Abstract Book - 15th Annual Congress of the European College of Sports Science)

Hochschulentwicklung innovativ gestalten. Das Projekt Locomotion an der Universität Paderborn

Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0

Flexible Resource Management for Self-X Systems: An Evaluation - Oberthür, Simon; Zaremba, Leszek; Lichte, Hermann Simon (2010 13th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Der Computer- und Videospielmarkt. Eine (medien)ökonomische Erfolgsgeschichte - Müller-Lietzkow, J.; Meister, Dorothee M. (Digitale Spielkultur)

Wissens- und Kommunikationsprozesse ethisch beratender Gremien in digitalen Gestaltungsformen - Meister, Dorothee M.; Kamin, A.-M.; Urban, D. (Medien – Wissen – Bildung. Explorationen visualisierter und kollaborativer Wissensräume)

Strategien der Professionalisierung in der Hochschuldidaktik - Urban, D.; Meister, Dorothee M. (ZFHE Zeitschrift für Hochschulentwicklung)

Lust und Schrecken medialer Gewalt. Medienpädagogische Überlegungen zum Fernsehverhalten Jugendlicher - Meister, Dorothee M.; Sander, U. (Jugend – Medien – Kultur. Medienpädagogische Konzepte und Projekte. Dieter Baacke Preis Handbuch 5)

Digitale Lernwelten in der Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Kamin, A.-M. (Digitale Lernwelten. Konzepte, Beispiele und Perspektiven)

Secure Naming for a Network of Information - Dannewitz, Christian; Golic, Jovan; Ohlman, Borje; Ahlgren, Bengt (2010 INFOCOM IEEE Conference on Computer Communications Workshops)

Emergenz neuer Lernkulturen – Bildungsaneignungsperspektiven im Web 2.0 - Meister, Dorothee M.; Meise, Bianca (Jahrbuch Medienpädagogik)

Medien im Erwachsenenalter - Meister, Dorothee M.; Kamin, A.-M. (Handbuch Mediensozialisation)

Wissens- und Kommunikationsprozesse ethisch beratender Gremien in digitalen Gestaltungsformen - Meister, Dorothee M.; Kamin, A.-M.; Urban, D. (Medien - Wissen - Bildung: Explorationen visualisierter und kollaborativer Wissensräume)

Digitale Lernwelten in der Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Kamin, A.-M. (Digitale Lernwelten. Konzepte, Beispiele und Perspektiven)

Medienkompetenz, Web 2.0 und mobiles Lernen - Editorial - Herzig, B.; Meister, Dorothee M.; Moser, H.; Niesyto, H. (Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0)

Das Pojekt Locomotion. (Low-Cost Multimedia Organisation & Production) - Gerholz, Karl-Heinz; Hauenschild, Wilfried; Klieber, Sebastian; Meister, Dorothee M.; Schäfer, Wilehlm ((s.dort))

Die E-Learning-Strategie der Universität Paderborn. Kompetenzorientierte Wissensarbeit ermöglichen - Hauenschild, Wilfried; Meister, Dorothee M.; Schäfer, Wilhelm ((s.dort))

Asynchronous Parallel Reliefboard Computation for Scene Object Approximation - Fischer, Matthias; Jähn, Claudius; Suess, Tim (Eurographics Symposium on Parallel Graphics and Visualization (EGPGV))
We present a parallel algorithm for the rendering of complex three-dimensional scenes. The algorithm runs across heterogeneous architectures of PC-clusters consisting of a visualization-node, equipped with a powerful graphics adapter, and cluster nodes requiring weaker graphics capabilities only. The visualization-node renders a mixture of scene objects and simplified meshes (Reliefboards). The cluster nodes assist the visualization-node by asynchronous computing of Reliefboards, which are used to replace and render distant parts of the scene. Our algorithm is capable of gaining significant speedups if the cluster's nodes provide weak graphics adapters only. We trade the number of cluster nodes off the scene objects' image quality.

Evaluation of a c-Load-Collision-Protocol for Load-Balancing in Interactive Environments - Suess, Tim; Wiesemann, Timo; Fischer, Matthias (2010 IEEE Fifth International Conference on Networking, Architecture, and Storage)
Many professional cluster systems consist of nodes with different hardware configurations. Such heterogeneous environments require different load-balancing techniques than homogenous environments. The c-load-collision-protocol is able to achieve good results for data-management purposes. Using this protocol, we propose a way for load-balancing in interactive rendering environments. For this work, we implemented a parallel rendering system and took different picking strategies into account to compare the results. The advantage of our approach compared to other approaches is that we group the available nodes of a cluster into two different categories, based on the hardware abilities. Some nodes are used solely for rendering, while others serve as secondary storage and to assist the former ones by performing auxiliary calculations.

Gewichtetes c-Collision-Protokoll zur Balancierung eines parallelen Out-of-Core-Renderingsystems - Suess, Tim; Wiesemann, Timo; Fischer, Matthias (Augmented & Virtual Reality in der Produktentstehung)
Typischerweise sind die Knoten eines PC-Clusters nicht mit leistungsfähigen Grafikkarten ausgestattet. Dennoch bieten Cluster-Betreiber einige wenige Rechenknoten an, die mit Highend-Grafikkarten ausgestattet sind, um beispielsweise eine PowerWall zu betreiben. Wenn zwischen diesen unterschiedlichen Knotentypen ein schnelles Netzwerk existiert, kann die Bilderzeugung durch die Knoten mit schwacher Grafikkarte beschleunigt werden. Dabei können die unterschiedlichen Knotentypen unterschiedliche Aufgabe bearbeiten. In einem solchen heterogenen System, müssen die unterschiedlichen entstehenden Lasten auf andere Weise verteilt werden, als in einem System, bei dem alle Knoten gleich ausgestattet sind. Wir präsentieren in dieser Arbeit Lastbalancierungsmechanismen, die in einem parallelen Out-of-Core-Renderingsystem für heterogene PC-Cluster eingesetzt werden.

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

First-principles calculation of electronic excitations in solids with SPEX - Schindlmayr, Arno; Friedrich, Christoph; Şaşıoğlu, Ersoy; Blügel, Stefan (Modern and Universal First-Principles Methods for Many-Electron Systems in Chemistry and Physics)
We describe the software package SPEX, which allows first-principles calculations of quasiparticle and collective electronic excitations in solids using techniques from many-body perturbation theory. The implementation is based on the full-potential linearized augmented-plane-wave (FLAPW) method, which treats core and valence electrons on an equal footing and can be applied to a wide range of materials, including transition metals and rare earths. After a discussion of essential features that contribute to the high numerical efficiency of the code, we present illustrative results for quasiparticle band structures calculated within the GW approximation for the electronic self-energy, electron-energy-loss spectra with inter- and intraband transitions as well as local-field effects, and spin-wave spectra of itinerant ferromagnets. In all cases the inclusion of many-body correlation terms leads to very good quantitative agreement with experimental spectroscopies.

Electronic structure and effective masses in strained silicon - Bouhassoune, Mohammed; Schindlmayr, Arno (Physica Status Solidi C)
The structural and electronic properties of strained silicon are investigated quantitatively with ab initio computational methods. For this purpose we combine densityfunctional theory within the local‐density approximation and the GW approximation for the electronic self‐energy. From the variation of the total energy as a function of applied strain we obtain the elastic constants, Poisson ratios and related structural parameters, taking a possible internal relaxation fully into account. For biaxial tensile strain in the (001) and (111) planes we then investigate the effects on the electronic band structure. These strain configurations occur in epitaxial silicon films grown on SiGe templates along different crystallographic directions. The tetragonal deformation resulting from (001) strain induces a valley splitting that removes the sixfold degeneracy of the conduction‐band minimum. Furthermore, strain in any direction causes the band structure to warp. We present quantitative results for the electron effective mass, derived from the curvature of the conduction band, as a function of strain and discuss the implications for the mobility of the charge carriers. The inclusion of proper self‐energy corrections within the GW approximation in our work not only yields band gaps in much better agreement with experimental measurements than the localdensity approximation, but also predicts slightly larger electron effective masses.

SkewCCC+: A Heterogeneous Distributed Hash Table - Bienkowski, Marcin; Brinkmann, André; Klonowski, Marek; Korzeniowski, Miroslaw (Proceedings of the 14th International Conference On Principles Of Distributed Systems (Opodis))

The MoSGrid Gaussian Portlet - Technologies for the Implementation of Portlets for Molecular Simulations - Wewior, Martin; Packschies, Lars; Blunk, Dirk; Wickeroth, Daniel; Warzecha, Klaus-Dieter; Herres-Pawlis, Sonja; Gesing, Sandra; Breuers, Sebastian; Krüger, Jens; Birkenheuer, Georg; Lang, Ulrich (Proc. Int. Workshop on Scientific Gateways (IWSG))

Workflow Interoperability in a Grid Portal for Molecular Simulations - Gesing, Sandra; Marton, Istvan; Birkenheuer, Georg; Schuller, Bernd; Grunzke, Richard; Krüger, Jens; Breuers, Sebastian; Blunk, Dirk; Fels, Gregor; Packschies, Lars; Brinkmann, André; Kohlbacher, Oliver; et al. (Proc. Int. Workshop on Scientific Gateways (IWSG))

Reliability Analysis of Declustered-Parity RAID 6 with Disk Scrubbing and Considering Irrecoverable Read Errors - Gao, Yan; Meister, Dirk; Brinkmann, André (Proc. IEEE Int. Conf. on Networking, Architecture and Storage (NAS))

Balls into Bins with Related Random Choices - Berenbrink, Petra; Brinkmann, André; Friedetzky, Tom; Nagel, Lars (Proc. Int. Symp. on Parallelism in Algorithms and Architectures (SPAA))